2001
DOI: 10.1016/s0008-6363(00)00232-7
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization in the rabbit hindlimb: dissociation between capillary sprouting and arteriogenesis

Abstract: Following femoral artery removal in the rabbit, the time course of angiogenesis and arteriogenesis were clearly distinct. Tissue ischemia and/or VEGF may stimulate capillary sprouting, but this response does not translate to a significant improvement in collateral flow. The growth and development of the larger collateral vessels was correlated with a large functional improvement in collateral flow, and occurred at a time when VEGF levels were undetectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
160
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 32 publications
16
160
2
1
Order By: Relevance
“…Using our method in a rat model of acute femoral artery occlusion, we observed neovascularization and subsequent recovery of perfusion via collaterals, consistent with previous reports [7,8]. Interestingly, in the preparations made early after induction of ischemia (directly postoperatively and at Day 7), a thrombus was present in the part of the ligated femoral artery distal to the site of occlusion.…”
Section: Discussionsupporting
confidence: 89%
“…Using our method in a rat model of acute femoral artery occlusion, we observed neovascularization and subsequent recovery of perfusion via collaterals, consistent with previous reports [7,8]. Interestingly, in the preparations made early after induction of ischemia (directly postoperatively and at Day 7), a thrombus was present in the part of the ligated femoral artery distal to the site of occlusion.…”
Section: Discussionsupporting
confidence: 89%
“…For example, it has been shown that the inclusion of BSA facilitates the release of growth factor from a polymer matrix (25). By carefully choosing these parameters, the release profile can be finely controlled, which may be especially important for optimizing the delivery of angiogenic factors (26,27). It has been demonstrated that in vivo release rates can be approximately twice the rates observed in vitro (24).…”
Section: Discussionmentioning
confidence: 99%
“…Capillary sprouting does not translate into improved flow, which depends on the growth of larger collateral vessels. 1 TNF-␣ has been localized to the macrophages of growing collateral arteries. 2 Using reverse transcriptase-polymerase chain reaction, we find TNF-␣ mRNA in the region of collateral artery growth 2 days after femoral artery occlusion in the mouse (C. Keith Ozaki, unpublished data, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1 Perivascular inflammation and monocyte/macrophage accumulation accompany this process. 2 Tumor necrosis factor-␣ (TNF-␣) is an important proximal mediator of inflammation.…”
mentioning
confidence: 99%